Influence of population and exercise protocol characteristics on hemodynamic determinants of post-aerobic exercise hypotension - Brito,L.C. (2014)
Due to differences in study populations and protocols, the hemodynamic determinants of post-aerobic exercise hypotension (PAEH) are controversial. This review analyzed the factors that might influence PAEH hemodynamic determinants, through a search on PubMed using the following key words: “postexercise” or “post-exercise” combined with “hypotension”, “blood pressure”, “cardiac output”, and “peripheral vascular resistance”, and “aerobic exercise” combined only with “blood pressure”. Forty-seven studies were selected, and the following characteristics were analyzed: age, gender, training status, body mass index status, blood pressure status, exercise intensity, duration and mode (continuous or interval), time of day, and recovery position. Data analysis showed that 1) most postexercise hypotension cases are due to a reduction in systemic vascular resistance; 2) age, body mass index, and blood pressure status influence postexercise hemodynamics, favoring cardiac output decrease in elderly, overweight, and hypertensive subjects; 3) gender and training status do not have an isolated influence; 4) exercise duration, intensity, and mode also do not affect postexercise hemodynamics; 5) time of day might have an influence, but more data are needed; and 6) recovery in the supine position facilitates systemic vascular resistance decrease. In conclusion, many factors may influence postexercise hypotension hemodynamics, and future studies should directly address these specific influences because different combinations may explain the observed variability in postexercise hemodynamic studies.